Analisis Pengaruh Produksi Kentang, Inflasi, dan Nilai Tukar Terhadap Ekspor Kentang Indonesia Periode 1993-2013 - Savitri, Putu Diah Layang; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Indonesia as one of the tourist destinations already known and famous in the world. Seen from the geographical size, Indonesia is the state having agraris natural resources abundant with the diversity of the potential of the regions. Economic activities in Indonesia not in spite of export activities of the agricultural sector in particular commodity is potato crops. The data used in this research is of secondary data time series obtained from Uncomtrade 1993-2013 year, Central of Statistic (BPS), and Indonesia Bank. This study using a quantitative approach that is shaped associative. The purpose of this study is to know the influence in unison and partial influence the production of potatoes, inflation, and the exchange rate to potatoes export, and to know the influence of most of the three dominant variable free to potatoes export Indonesia 1993-2013 period. The analysis shows simultaneously the influence of the production of potatoes, inflation, and the exchange rate significant to potatoes export. In partial, the influence of the production of potatoes and the exchange rate influential positive and significant, while inflation is not significant to potatoes export Indonesia 1993-2013 period. The most dominant variable influential free potato exports to Indonesia is the production of potato 1993-2013 period. Keywords: potato export, the production of potatoes, inflation, the exchange rate
Keywords: Potato Export, the Production of Potatoes, Inflation, the Exchange Rate